Estimates of glomerular filtration rate in critically ill patients with sepsis: comparisons of different equations - Md Ralib, Azrina; Ab. Rashid, Iqbalmunauwir; Mohd Hanafiah, Farah Nadia; Abdul Rahim, Shahir Asraf; Mat Nor, Mohd Basri (Kulliyyah of Medicine IIUM, 2022)
INTRODUCTION: Accurate assessment of glomerular filtration rate (GFR) is important in the critically ill. Kinetic estimate of GFR (keGFR) considers the changes of creatinine, creatinine production rate, and volume of distribution hence postulated to be a more accurate estimate of GFR, where there are rapidly changing kidney functions. We evaluated the association of the estimated GFR by established equations and keGFR with creatinine clearance (CrCl) measurement. MATERIALS AND METHODS: This is a prospective observational study of critically ill patients. Inclusion criteria were patients older than 18 years old with sepsis (clinical infection and increase in SOFA score>2), and plasma procalcitonin>0.5ng/ml. Plasma creatinine and Cystatin C (CysC) were measured on admission and 4 hours later, and the eGFR was calculated by the Cockcroft Gault (CG), MDRD, CKD-EPI, and keGFR equations, and compared to the CrCl measurement. RESULTS: A total of 70 patients were recruited. eGFR by all 4 equations strongly correlates with CrCl. keGFR had the least bias depicted by the mean differences nearest to zero (-18ml/min). Similarly, keGFRCysC had less bias than eGFRCysC, with a mean difference of -21ml/min. eGFRCG had the greatest precision depicted by the narrower SD lines, however, the precision of both keGFR were not much different compared to those of eGFRCG. CONCLUSIONS: In critically ill patients with sepsis, keGFRCr and keGFRCysC had the least bias and fair precision when compared to creatinine clearance measurement. In the absence of creatinine clearance measurement, keGFR calculations are useful as a surrogate for kidney function.